Liver transplantation - Asemi, S (Iran University of Medical Sciences, 1995)
However, history of liver transplantation has started in 1963, but after discovery of anti-rejection drugs such as cyclosporine in 1980s, this method has experienced. From 1984 more than 3000 patients underwent surgery and just 1680 patients in 66 liver transplantation centers have operated in 1988. Every patient suffers from severe liver diseases and is in terminal stage of this disease, must be observed in liver transplantation center for assessment and evaluation of treatment. Assessment includes history taking and usual liver examinations. Examination is necessary for ABO compatibility (for comparison liver donor and recipient) and screening for diagnosis of hepatitis and AIDS. Ultrasonography is performing for liver circulation assessment. Also, liver span is estimating by CT-scan. When all of diagnostic tests gathering, medical team categorizing patients who need to liver transplantation